2000
DOI: 10.1021/jp992511h
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Spin Forbidden Proton-Transfer Reactions:  3NO- + HA → 1HNO + A-

Abstract: 2 OH, and CH 3 OH) in the gas phase have been measured using Fourier transform ion cyclotron resonance (FT-ICR) spectrometry. Protontransfer efficiency was found to vary dramatically with both the structure and acidity of HA. This variation is attributed to different lifetimes of the collision complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…This report not only revised the pK a but also indicated that the relevant equilibrium was between singlet HNO and the triplet anion [Eq. (3)] (a conclusion already drawn by Janaway and Brauman for the gas phase [56] ). Subsequent experimental work by Shafirovich and Lymar [58] and theoretical re-evaluation by Bartberger and co-workers [57] have now provided a consensus agreement that the pK a of HNO is approximately 11.4.…”
Section: Nosupporting
confidence: 52%
“…This report not only revised the pK a but also indicated that the relevant equilibrium was between singlet HNO and the triplet anion [Eq. (3)] (a conclusion already drawn by Janaway and Brauman for the gas phase [56] ). Subsequent experimental work by Shafirovich and Lymar [58] and theoretical re-evaluation by Bartberger and co-workers [57] have now provided a consensus agreement that the pK a of HNO is approximately 11.4.…”
Section: Nosupporting
confidence: 52%
“…However, whereas the NO À anion has a triplet ground state (DE S-T ¼ 18 kcal/mol), the conjugate acid, HNO, is a ground state singlet (DE S-T ¼ 18.1 kcal/mol) (Janaway & Brauman, 2000). Therefore, adiabatic proton transfer requires intersystem crossing from the triplet to the singlet surface (Ellis & Ellison, 1983;Tennyson & Noble, 1986;Szmytkowski & Maciag, 1991).…”
Section: B Proton Transfer Reagentsmentioning
confidence: 99%
“…Therefore, adiabatic proton transfer requires intersystem crossing from the triplet to the singlet surface (Ellis & Ellison, 1983;Tennyson & Noble, 1986;Szmytkowski & Maciag, 1991). On the other hand, diabatic proton transfer, where spin is conserved, requires an additional 18 kcal/mol to overcome the singlet-triplet splitting in HNO (Janaway & Brauman, 2000) and is only energetically allowed for reagents with gas phase acidities lower than ca. 343 kcal/mol.…”
Section: B Proton Transfer Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (9,19). In the original study by Grätzel et al (4), difficulty in obtaining an accurate NO Ϫ concentration measurement directly after the radiolysis pulse (25,26) that the process of proton transfer involving spin state interconversion is slowed by as much as 10 7 , as compared with spin-conserving proton transfers.…”
Section: Nomentioning
confidence: 99%